Role of microalgae as a sustainable alternative of biopolymers and its application in industries - Dimri, Rohit; Mall, Shivangi; Sinha, Somya; Joshi, Naveen Chandra; Bhatnagar, Pooja; Rohit Sharma; Vinod Kumar; Gururani, Prateek (Plant Science Today, 2023)
The escalating accumulation of petroleum-based polymers has depleted resources and raised environmental concerns due to their non-recyclable and non-biodegradable nature. Consequently, there has been a growing interest in bio-based plastics, particularly algal-based biopolymers, which offer recyclability and eco-friendliness. Algae-derived polymers have distinct advantages, such as autotrophic growth reducing greenhouse gas emissions, rapid growth rate, low nutritional requirements, and resilience to harsh environments. Additionally, algae exhibit higher photosynthetic potential (10-20%) compared to terrestrial plants (1%-2%). The range of algal-derived polymers includes alginate, laminarin, fucoidan, carrageenan, agar, ulvan, polyhydroxyalkanoates (PHA), and poly-(Hydroxybutyrate) (PHB). However, further efforts are required to implement them on a large scale. This review highlights algae's potential as a raw material for biopolymer production, exploring their characteristics and applications in diverse industries like food and pharmaceuticals.